The effect of aerobic exercise on sleep disorder in menopausal women: a systematic review and meta-analyses - Yan Jing; Mingyi Liu; Honglin Tang; Nianxin Kong; Jingjie Cai; Zikang Yin (BMC Women's Health)
Abstract Objective This study systematically evaluated the effect of aerobic exercise on sleep disorders in menopausal women and proposed a practical program from the perspective of "what to practice," "how much to practice," and "how to practice." We proposed the program from the standpoint of training science. Methods Up to March 20, 2023, a total of 16 articles and 19 RCT studies were retrieved from Web of Science, PubMed, Springer, Science Direct, China Knowledge Network, Wanfang, and VIP. The Cochrane Risk of Bias Assessment Tool was used to assess the quality of the literature, and We used RevMan5.3and STATA 16.0 software to provide a systematic review of included studies. Results The overall effect of low- and moderate-intensity aerobic exercise interventions for sleep disorders in menopausal women had a moderate effect size (SMD = -0.52, P < 0.001), and the effect values between different intervention frequencies (I2 = 60%), intervention duration (I2 = 60), intervention periods (I2 = 70), exercise forms (I2 = 70), and practice methods (I2 = 70) had moderate heterogeneity. The most significant effect sizes were found for intervention frequency of 3 times/week (SMD = -0.57, P < 0.001); intervention duration of 70–90 min/session (SMD = -0.64, P = 0.004); intervention period of 8–10 weeks (SMD = -0.59, P = 0.35); and exercise form of static exercise ( SMD = -0.55, P = 0.003); and the practice mode was an individual exercise with the most significant effect size (SMD = -0.66, P < 0.01). Conclusion Low- and medium-intensity aerobic exercise intervention for sleep disorders in menopausal women has a good effect, but it is affected by training factors such as intervention frequency, intervention time, intervention period, exercise form, and practice mode; the best effect is achieved by adopting the dosage of 3 times/week, 70–90 min/times, and lasting for 8–10 weeks; aerobic intervention in the form of static exercise is the most effective; the best intervention effect is achieved by adopting the mode of individual exercise; but a group exercise approach improved exercise persistence in menopausal women.